RENCANA PENGEMBANGAN KAWASAN WISATA BENDUNGAN PIDEKSO KECAMATAN GIRIWOYO KABUPATEN WONOGIRI - Rohani, Elisa Dwi; Firstantin, Theresia Avila Rencidiptya; Sumantri, Danendra Kusumadewa (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2024)
AbstractThe development of dam as a tourist attraction is an important process to encourage economic development, as well as improve community welfare. The development of dam as a tourist attraction can be carried out through various ways, such as the development of tourist facilities, promotion and improvement of information to tourists, and increasing the active participation of the community in order to create new jobs. Local governments, as well as entrepreneurs and the community also play an important role in developing the potential of dam as a tourist attraction. The research approach carried out in this study will use a qualitative research approach, data collection methods with a) FGD, b) in-depth interviews, c) observation, d) literature studies, and e) documentation. The development of the Pidekso Dam pays attention to sustainability, local uniqueness, and existing market potential, by utilizing these potentials, can develop diverse and attractive tourism for tourists. The Pidekso Dam is built with a zoning system is one part of visitor management techniques that are useful for maintaining carrying capacity, regulating visitor flow patterns, facilitating the maintenance of facilities, optimizing existing land, avoiding collisions or conflicts between the interests of facilities and activities and ensuring that the development carried out has been planned. In addition, the development of the Pidekso Dam area also pays attention to non-physical aspects, including the management plan of visitor service centers, the development plan of tourism products, the plan for community involvement and empowerment, the plan for the management of the tourist attraction environment, and the plan for the development of the tourist market.Keywords: Planning; Development; Tourism; Pidekso; WonogiriAbstrakPengembangan wisata bendungan merupakan suatu proses yang penting untuk mendorong perkembangan ekonomi, serta meningkatkan kesejahteraan masyarakat. Pengembangan wisata bedungan dapat dilakukan melalui berbagai cara, seperti pengembangan fasilitas wisata, promosi dan peningkatan informasi kepada wisatawan, serta meningkatkan partisipasi aktif masyarakat dalam rangka menciptakan lapangan pekerjaan baru. Pemerintah daerah, serta pengusaha dan masyarakat juga berperan penting dalam mengembangkan potensi wisata bedungan. Pendekatan penelitian yang dilaksanakan dalam penelitian ini akan mengunakan pendekatan penelitian kualitatif, metode pengumpulan data dengan a) FGD, b) wawancara mendalam, c) Observasi, d) studi pustaka, dan e) dokumentasi. Pengembangan Bendungan Pidekso memperhatikan keberlanjutan, keunikan lokal, dan potensi pasar yang ada, dengan memanfaatkan potensi-potensi tersebut, dapat mengembangkan pariwisata yang beragam dan menarik bagi wisatawan. Bendungan Pidekso dibanguan dengan sistem zonasi merupakan salah satu bagian dari visitor management techniques yang bermanfaat untuk menjaga daya dukung, mengatur pola arus pengunjung, memudahkan pemeliharaan fasilitas, optimalisasi lahan yang ada, menghindari benturan atau konflik antar kepentingan fasilitas dan aktivitas dan meyakinkan bahwa pengembangan yang dilakukan sudah terencana. Selain itu pengembangan kawasan Bendungan Pidekso juga memperhatikan aspek non fisik diantaranya adalah rencana pengelolaan pusat-pusat pelayanan pengunjung, rencana pengembangan produk pariwisata, rencana pelibatan dan pemberdayaan masyarakat, rencana pengelolaan lingkungan daya tarik wisata, serta rencana pengembangan pasar wisatawan.Kata Kunci: Rencana Pengembangan; Wisata; Bedungan Pidekso; Wonogiri